How to reduce the adverse effects of weight stigma on the quality of life: a preferred reported items for systematic reviews and meta-analyses (PRISMA) - Ramsamy, Guillaume; Mosbah, Helena; Faure, Jean Pierre; Plault, Vanina; Albouy, Marion; Esnard, Catherine (Frontiers in Psychology, 2024)
IntroductionObesity, affecting 38% of adults globally, carries economic burdens and health risks like cardiovascular disease and diabetes. Weight-loss programs often face challenges due to stigma and poor body image, impacting individuals’ quality of life. Research on interventions targeting weight stigma is lacking, emphasizing the need for comprehensive approaches addressing psychological and behavioral aspects for effective care.MethodsA systematic literature review was conducted according to PRISMA guidelines. We searched into three databases (PubMed, APA PsycArticles/PsycInfo, and Web of Science) articles published between 1975 and 2024. Studies were eligible if they involved people living with overweight or obesity who participate in a psychological program targeting, or not, weight stigma and if at least one outcome was related to weight stigma.ResultsWe selected 24 studies published between 2009 and 2022, the majority concerning English-speaking countries. Reduction in weight stigma was observed in 23/24 studies, particularly through cognitive-behavioral techniques (18/24 studies), while others studies emphasized individual predispositions and the need for longer, and denser interventions.ConclusionThree relevant characteristics emerged from the studies analysed: content, duration and tools. Cognitive-behavioral techniques were central, aiding participants in managing their condition and coping with stigma. Interventions reducing Weight Bias Internalization (WBI) led to improved psychosocial determinants, yet the mechanisms remain unclear. Future research should address intervention duration, participant involvement, and the association between WBI and psychosocial factors to enhance outcomes and understanding.